Simulation Evaluation of Cardiac Assist Devices - Bai, J.; Bing, Z. (Methods of Information in Medicine, 2000)
During past decades, various cardiac assist devices were invented. These cardiac assist devices can be classified into two categories: parallel connected or sequentially connected to the natural heart. In the past, more attention was paid to the assistance of the device provided to the failing heart and most research was conducted towards that goal. While less attention was paid to the “dose” of the assistance for rehabilitation of the natural heart. In our study, the hemodynamic effects of parallel as well as sequential cardiac assist devices are investigated in terms of the working load to the natural heart, and the oxygen supply and consumption of the natural heart. Preliminary results show that the sequential assistance could reduce the working load of the natural heart as well as increase the coronary flow. The results also indicate that the control scheme of the cardiac assist device has effect on the oxygen supply and consumption of the natural heart. There is optimal “dose” of assistance for the rehabilitation of the natural heart.
Keywords: Ventricular Assist Devices; Regional Ischemia; Cardiac Function Recovery; Computer Simulation